Treating age-related multimorbidity: the drug discovery challenge. Issue 8 (August 2020) - Ermogenous, Christos; Green, Charlotte; Jackson, Thomas; Ferguson, Michael; Lord, Janet M.
Highlights: Multimorbidity is a common feature of old age and is accompanied by polypharmacy. Targeting the core processes of ageing offers a new drug discovery approach for multimorbidity. Inhibiting ageing processes reduces multiple diseases in mouse models. Current clinical trials with repurposed drugs have shown clinical benefit Targeting specific ageing processes with novel drugs may allow a more precise intervention. Patients with multimorbidities have shorter life expectancy and their clinical management is more complex and expensive for healthcare systems currently focused on treating single diseases. Given that age is the major risk factor for multimorbidity, the challenge of treating these patients will only increase in coming years. Here, we review the case for targeting the core processes that drive the ageing phenotype as a novel pharmaceutical approach to multimorbidity. There is growing evidence that targeting ageing mechanisms can reduce or delay age-related diseases in animal models, and the first reports of clinical trials are now appearing. Although these trials currently focus on repurposed drugs, we propose several novel targets that would more specifically target ageing processes and thereby reduce multimorbidity and polypharmacy in future generations. Teaser: Advanced age is the major risk factor for multimorbidity. Current clinical practice treats the individual age-related diseases, resulting in polypharmacy. Thus, targeting the biological processes that drive ageing could prevent both multimorbidity and polypharmacy.